Link Layer Based TCP Optimisation for Disconnecting Networks - Scott, James; Mapp, Glenford (ACM Computer Communications Review, 2003)
This paper discusses a link layer approach to improving TCP performance in the face of periodic network disconnections. Network disconnections are encountered in many scenarios, including being out-of-range in a wireless network, during network handoff, and also in the case of Networked Surfaces, a novel LAN technology which provides the motivation for this work.